Avaliação da padronização dos procedimentos nas salas públicas de vacinas do município de Itabaiana, Sergipe, Brasil (Brazilian Journal of Health Research, 2018)
Assessment of Standardization of the Procedures in the Public Vaccination Facilities in the Municipality of Itabaiana, Sergipe, Brazil